2014
DOI: 10.1002/2014ja019959
|View full text |Cite
|
Sign up to set email alerts
|

The Midlatitude Summer Night Anomaly as observed by CHAMP and GRACE: Interpreted as tidal features

Abstract: This paper presents a description of the Midlatitude Summer Night Anomaly (MSNA) in terms of solar tidal signatures, based on in situ observations from CHAMP (CHAllenging Minisatellite Payload) and GRACE (Gravity Recovery and Climate Experiment) during the solar minimum years 2008 and 2009. Our analysis is focusing on 40• to 60• magnetic latitude ranges in both hemispheres, where the reversed diurnal variations of the electron density are strongest. The results revealed that in the Southern Hemisphere the long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
60
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(79 citation statements)
references
References 50 publications
17
60
1
1
Order By: Relevance
“…The most prominent tidal components in mass density and zonal wind are the diurnal tides D0 and DW2 and the semidiurnal tides SW1 and SW3. This is consistent with the tidal signatures in the F region electron density at midlatitudes as reported by Xiong and Lühr (2014). These same tidal components are observed both in the thermospheric and ionospheric quantities, supporting a mechanism that the non-migrating tides in the upper atmosphere are excited in situ by ion-neutral interactions at midlatitudes, consistent with the modeling results of Jones Jr.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…The most prominent tidal components in mass density and zonal wind are the diurnal tides D0 and DW2 and the semidiurnal tides SW1 and SW3. This is consistent with the tidal signatures in the F region electron density at midlatitudes as reported by Xiong and Lühr (2014). These same tidal components are observed both in the thermospheric and ionospheric quantities, supporting a mechanism that the non-migrating tides in the upper atmosphere are excited in situ by ion-neutral interactions at midlatitudes, consistent with the modeling results of Jones Jr.…”
supporting
confidence: 89%
“…They further explained that the standing diurnal tide (D0) dominates the vertical neutral wind causing the southern MSNA feature, and the tide manifests itself as a diurnal eastward-propagating wave-1 pattern. Our recent study confirmed the eastward movement of the MSNA in both hemispheres from in situ measurements of the CHAMP and GRACE missions (Xiong and Lühr, 2014). From the tidal perspective, the prominent MSNA features have further been interpreted as the simultaneous constructive interferences of the tidal components D0, DW2, and stationary planetary wave SPW1 in the Southern Hemisphere, and DE1, D0, and DW2 in the Northern Hemisphere.…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations